Switching on plant innate immunity signaling systems : bioengineering and molecular manipulation of PAMP-PIMP-PRR signaling complex /: bioengineering and molecular manipulation of PAMP-PIMP-PRR signaling complex. ([2016]) - Vidhyasekaran, P
No abstract available